The Importance of the Judge’s Assessment of the Penalty in Achieving Family Stability: The Crime of Marital Violence as a Model - Madjidi, Larbi (Journal of Legal Studies and Researches, 2023)
The interest of society in punishing the offender, and the interest of preserving the cohesion of the family entity, through the authority of the criminal judge in estimating and adapting punishment, especially penalties family-related crimes; such as the crime of spousal violence by a husband against his wife.